Juegos infantiles y conducta en el aula en niños de la Institución Educativa Inicial N° 728, Caballococha 2022 - Perez Laban, Raquel (2023)
The problem of the present study arises from the question: What relationship exists between children's games and behavior in the classroom in children of the initial educational institution No. 728 Caballococha in 2022? the main objective being to relate children's games and the behavior in the classroom in the children of the initial educational institution N° 728. The type of relational investigation with field, crosssectional and bivariate design was applied. The observation technique and observation guides were used as data collection instruments validated in advance by experts. The data was obtained from 149 school children who made up the population and sample respectively. Conclusion: Kendall's Tau-b coefficient with a value of 0.217 and a significance of 0.035 (p < 0.05), indicates an ordinal relationship between the levels of development of children's games and behavior in the classroom, according to the level of development of the children. children's games the level of behavior in the classroom increases, in addition the student’s t test statistic = 10,131; p-value (bilateral significance) = 0.013, less than 0.05, indicates a significance level of 5%, so there is a statistically significant relationship between children's games and classroom behavior in children from Initial Educational Institution N ° 728 of Caballococha, which demonstrates the hypothesis raised in the investigation.